PENGARUH ABU SEKAM PADI DAN KOMPOS TKKS TERHADAP PERTUMBUHAN DAN HASIL TANAMAN CABAI (Capsicum annuum. L) DI MEDIUM GAMBUT - Eka Safitri1; Murniati Murniati; Al Ikhsan Amri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
This research aims to know the effect of rice husk ash interaction and OPEB compost and get the best combination to the growth and yield pepper plant in peat medium. This research was conducted at the experimental farm of the Agriculture Faculty, University of Riau started in January to June 2017. This experiment was conductin the form of a 3 x 3 factorial arranged according to a completely randomized design. The first factor is the grain of rice husk ash 0, 5 and 10 ton/ha. And the second factor is the grain OPEB compost 0, 5 and 10 ton/ha. Parameters observed are hight of plant, stem diameter, header width, day flowering, number of fruit crops, weigth of fruit crops. The results of observation data were further analyze by Duncan new multiple range test at 5% level. The results showed that the interaction of rice husk ash and OPEB compost gave effect on all parameters, Rice husk ash 10 ton/ha and OPEB compost 10 ton/ha is the best treatment to the growth and yield of pepper plants compared to other treatment. Keywords : Rice husk ash, compost of oil palm empty bunches, pepper plant, peat medium.